Emotional competencies in emerging adolescence: relations between teacher ratings and student self-reports. Issue 1 (2nd January 2019) - Smith, Shanen; Dutcher, Keeley; Askar, Malak; Talwar, Victoria; Bosacki, Sandra
Abstract: This cross-sectional study examines gender-informed teachers' and early adolescents' reports of emotional competencies within the school setting. The sample for the current study consisted of 290 emerging adolescents (114 boys, 170 girls) recruited from 24 schools. Social-emotional competencies were assessed by students' self-report questionnaires and teacher and parent reports. Results showed significant positive associations between teacher-rated emotional competencies and emerging adolescents' self-reports with three of the four Interpersonal Reactivity Index subscales (Perspective Taking, r  = .231, p  = .000; Fantasy, r  = .303, p  = .000; and Empathetic Concern, r  = .196, p  = .007). Significant gender differences were also found as both adults and adolescents' rated girls as showing greater emotional competencies than boys. Results are discussed in terms of future research directions and implications for educational strategies and practices to help build prosocial and emotional abilities and behaviours.